PROFIL KETERAMPILAN BERKOMUNIKASI SISWA SMA MENGGUNAKAN METODE FENETIK DALAM PEMBELAJARAN KLASIFIKASI ARTHROPODA - Oktaviani, Feni; Hidayat, Topik (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2010)
We conducted a research about communication skill of secondary biology student in Arthropode classification using phenetic method. Data were obtained from written report and oral presentation. There were five indicators used to analyze communication skill in oral presentation, which included their ability to express opinion themselves and hearing the opinion from other, their ability to master the concept to be presented, their ability to communicate of results systematically and clearly, their ability to question, and their ability to answer. Five indicators used in written report were their ability to choose informative character to build fenogram, their ability to undergo step by step, resulted phenogram, their ability to interpret the results, and their ability to make a report. Results showed that communication skill in oral were good enough (63.75%), but low (56.25%) in written. Based on interview, however, students felt comfortable when teacher used the phenetic method to understand classification of Arthropode. This method has markedly stimulated the students to study actively in the classroom.